Justice outsourced: the therapeutic jurisprudence implications of judicial decision-making by nonjudicial officers - Perlin, Michael L.; Frailing, Kelly (Temple University Press, 2022)
"This book examines what can be lost when nonjudicial officials step into judicial roles and how the rights, dignity, and fairness that judges offer within justice procedures might be safeguarded according to the values of therapeutic jurisprudence"--